2019
DOI: 10.53986/ibjm.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Magnetite Nanoparticles (MCS-B) on Human Platelet Aggregation

Abstract: Background: Currently, one of the main problems that happens in the treatment by extracorporeal methods of hemosorption is systemic shifts in homeostasis. Among these complications the most significant are blood cells traumatization and hemorrhage. Direct physical contact of blood with sorbent surface causes activation of a multistage reaction of thrombosis. Now, new methods of hemosorption using non-traumatic sorbents are being actively developed. Wide introduction of nanotechnological preparations (magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Studies have shown that magnetic fields can affect blood flow through orientation of blood cells and can potentially limit thrombosis through promoting blood flow . Additionally, studies have shown that magnetic nanoparticles reduce platelet aggregation . Therefore, an important extension of this research would be testing magnetized BNC for thrombogenicity.…”
Section: Bacterial Nanocellulose As Artificial Vascular Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that magnetic fields can affect blood flow through orientation of blood cells and can potentially limit thrombosis through promoting blood flow . Additionally, studies have shown that magnetic nanoparticles reduce platelet aggregation . Therefore, an important extension of this research would be testing magnetized BNC for thrombogenicity.…”
Section: Bacterial Nanocellulose As Artificial Vascular Graftsmentioning
confidence: 99%
“… 163 Additionally, studies have shown that magnetic nanoparticles reduce platelet aggregation. 164 Therefore, an important extension of this research would be testing magnetized BNC for thrombogenicity.…”
Section: Bacterial Nanocellulose As Artificial Vascular Graftsmentioning
confidence: 99%
“…The enumerated parameters for reliable have influence on haemorreology and state of microcirculation on the whole. The high local concentration of magnetite in vessels is caused by disturbances of blood circulation, microcirculation and hypoxia of tissues [10,11]. It is dangerous in main vital organs: brain, heart, lungs, liver and kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in the choice of theme of the present investigation. The task was set in an experiment on animals to check possibility of the use of the before worked-out and studied methodology of using standardized form of magnetite nanoparticles [11][12][13][14][15][16][17][18][19][20]. The main purpose is to investigate the ultrastructural reconstructions in hepatic cells after using standardized powder form of magnetite nanoparticles Micromage-B [21][22][23].…”
Section: Introductionmentioning
confidence: 99%